Cu-Ag nanoparticles positively modulating the endophytic bacterial community in tomato roots affected by bacterial wilt - Ning, Weimin; Bao, Xuefeng; Jiang, Lei; Yang, Mei; Lei, Tianhao; Liu, Maoyan; Liu, Yong (Frontiers in Microbiology, 2025)
IntroductionTomato bacterial wilt (TBW) is a destructive soil-borne bacterial infection caused by Ralstonia solanacearum. Various nanoparticles have been employed as antibacterial agents to manage TBW via soil application. However, research on the effects of nanoparticles on plant endophytes remains limited.MethodsHere, an analysis of the endophytic bacterial community was performed on healthy and infected tomatoes that were treated with Cu-Ag nanoparticles and thiodiazole-copper via high-throughput 16S rRNA gene amplicon sequencing.ResultsThe relative abundance levels of beneficial bacteria, including Acidobacteriota, Firmicutes, Actinobacteriota, and Myxococcota, were higher in infected tomato roots treated with Cu-Ag nanoparticles compared with thiodiazole-copper. Functional predictions show that Cu-Ag nanoparticles may affect pyruvate metabolism, oxidative phosphorylation, purine metabolism, carbon metabolism, secondary metabolite production, and the metabolic pathways associated with microbial communities.DiscussionThese results could reveal the mechanism by which nanoparticles influence the endophytic microbiomes of plant roots and direct the rational application of nanoparticlesin sustainable agriculture.